Analisis Pelaksanaan Strategi Peningkatan Penerimaan Pajak Air Tanah Pada Unit Pelayanan Pemungutan Pajak Daerah Cempaka Putih Tahun 2017 – 2020 - Fahmi Muhammad Perwira; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Groundwater tax is one of state revenues sourcing from tax collection. As regulated in Regulation of the Governor of DKI JAKARTA Number 38 Year 2017. Recorded land subsidence has occurred since the early of 1990s. To anticipate, Government of DKI Jakarta Province has stipulated groundwater utilization tax through Governor Regulation No. 10 Year 1998 to encourage community and industry to use Water Company’s water and reduce excessive groundwater extraction which will threaten environmental sustainability. This research aims to determine the implementation of strategy for increasing groundwater tax revenue along with its problems and efforts. Based on conceptual model of Machfud Sidi k and Chairil Anwar Pohan. By using qualitative research methods descriptive approach, using data collection techniques by observation, interview and documentation. The results show that strategy for increasing groundwater tax revenue at UPPPD Cempaka Puti h has not worked well, because there are still many taxpayers who have not re-registered, the lack of expansion of new taxpayers, human resources are still not educating taxpayers and have not fully implemented sanctions because of the low supervision. In this research, it is necessary to suggest that strategy for increasing groundwater tax revenue at UPPPD Cempaka Putih in order data collection and supervision activities are carried out by tax authorities directly, so that tax authorities are more active i n socializing the management and licensing of groundwater tax.